Slashed Interiors: Text/Space - Siddiqui, Igor (Interiority, 2020)
This essay explores the relationship between text and space by considering the notion of writing interiors as a form of creative practice. The research focuses on the textual and spatial uses of the punctuation mark slash (/), as evidenced in a range of text-based works by Barbara Kruger, Glenn Ligon, Dom Sylvester Houédard, Anni Albers, and other artists. The first part of the essay surveys the typographic character’s varied uses in written language; the second part considers its role within artwork titles, namely how its presence shapes spatial interpretations of each artwork in question; in the third part, preceding the conclusion, the focus is on the use of the slash as a mark that is both material and graphic. The resulting interpretations support a call for a change in the conversation about the relationship between writing and interiors.